Physiological Significance of NAD Kinases in Cyanobacteria - Ishikawa, Yuuma; Kawai-Yamada, Maki (Frontiers in Plant Science, 2019)
Unicellular cyanobacteria are thought to be the evolutionary ancestors of plant chloroplasts and are widely used both for chemical production and as model organisms in studies of photosynthesis. Although NAD(P)(H) are targets of metabolic engineering, the physiological roles of NAD(P)(H) in cyanobacteria long have been underestimated. In cyanobacteria such as the model species Synechocystis sp. PCC 6803, most metabolic pathways share a single compartment. This complex metabolism raises the question of how cyanobacteria control the amounts of the redox pairs NADH/NAD+ and NADPH/NADP+ in the cyanobacterial metabolic pathways. For example, photosynthetic and respiratory electron transport chains share several redox components in the thylakoid lumen, including plastoquinone, the cytochrome b6f (cyt b6f), and the redox carriers plastocyanin and cytochrome c6. In the case of photosynthesis, NADP acts as an important electron mediator on the acceptor-side of photosystem I (PSI) in the linear electron chain as well as in the plant chloroplast. Meanwhile, in respiration, most electrons derived from NADPH and NADH are transferred by NAD(P)H dehydrogenases. Therefore, it is expected that Synechocystis employs unique NAD(P)(H) -pool control mechanisms to regulate the mixed metabolic systems involved in photosynthesis and respiration. This review article summarizes the current state of knowledge of NAD(P)(H) metabolism in Synechocystis. In particular, we focus on the physiological function in Synechocystis of NAD kinase, the enzyme that phosphorylates NAD+ to NADP+.